Microwave-generated Bionanocomposites for Solubility Enhancement of Nifedipine (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Oral dosage form of drug mainly depends on its absorption, dissolution, and diffusion through gastrointestinal membrane is promising approach/mechanism. The major challenge in case of most of the drugs is aqueous solubility. This work focusing on preparation of bionanocomposites (BNCs) of such poorly water-soluble drug by microwave induced diffusion (MIND) technique to enhance drug solubility in aqueous medium and increase its rate of dissolution. Considering to this the drug was selected from Biopharmaceutical Classification System class-II drug. Materials and Methods: Nifedipine and newer natural carriers such as Moringa oleifera Gum and Aegle marmelos (L.) were selected and used for BNCs preparation which was based on their wetting and surface active agent property. BNCs were prepared by most convenient and cost-effective MIND technique. The enhanced solubility and dissolution of BNCs were assessed by in vitro solubility and dissolution studies. Results and Discussion: It was demonstrated that the dissolution of nifedipine enhanced with an increase in polymer concentration. Mostly, the optimized ratio of drug and polymer from the entire composite was found Nifedipine Moringa Oleifera Bionanocomposite (NIMONC) 1:2 and Nifedipine Aegle Marmelos Bionanocomposite (NIAMNC) 1:3, BNCs with natural carriers which shown significant enhancement in solubility. Characterizations of prepared BNCs have been done by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction studies, and scanning electron microscopy. Conclusion: Enhancement in the solubility might be because of formation of drug dispersion at micro and nanoscale level. Hence, the development of BNCs is a promising approach to increase solubility and rate of dissolution of poorly water-soluble drug.